HUBUNGAN FREKUENSI PAPARAN MEDIA PORNOGRAFI DENGAN FREKUENSI PERILAKU MASTURBASI REMAJA PUTRA DI SMK WONGSOREJO GOMBONG KEBUMEN - Sunarsih, Sri; Purwanti, Sugi; Khosidah, Amik (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2010)
Adolescent is transition period, marked with puberty where happened sexual maturity and psikososial which interconnected, change of puberty give contribution to become oneof seksuality at adolescent, so that when arise sexual motivation, adolescent need to channel it. One of way to channel sexual motivation is doing masturbating. One of the factor able to influence masturbating that is pornography media. This research aim to know relation of frequency an exposure pornography media with behavioral frequency of adolescent boy masturbating in SMK Wongsorejo Gombong, Kebumen Year 2010. This Research use method research of analytic survey method by cross sectional approach. Population in adolescent all these research of Boy in SMK Wongsorejo Gombong Kebumen Year 2010 amounting to 1181 student, and amount of sample 92 student. Method analyse at this research use test of Chi square. Frequency an exposure of pornography media at most that is > 1 x every month counted 41 (45%) responder, behavioral frequency of masturbating > 12 x every month (51 %), what is â‰¤ 12 x every month (49%), result of calculation of pornography media exposure frequencyÂ  with behavioral frequency of adolescent masturbating of boy in obtaining value Ï (probability) 0,000 There is relation of exposure an pornography media frequency with behavioral frequency of adolescent boy masturbating in SMK Wongsorejo Gombong, Kebumen Year 2010 (Ï : 0,000). Adolescent of boy shouldnâ€™t excessively look on, see/reading pornography media, don't often masturbating, and better be active follow activity which are positive like activity of OSIS/extracurricular. Â  Key Words : exposure of pornography media, adolescent boy masturbating